The Effect Of Power Spectral Density On The Electroencephalography Of Autistic Children Based On The Welch Periodogram Method - Melinda Melinda; I Ketut Agung Enriko; Muhammad Furqan; Muhammad Irhamsyah; Yunidar Yunidar; Nurlida Basir (LPPM Institut Teknologi Telkom Purwokerto, 2024)
Non-Indexed Publication